Pelatihan Anggaran dan Tabungan untuk Meningkatkan Pendapatan Anggota Koperasi Kuntum Mekar di Kabupaten Pandeglang - Bakti Toni Endaryono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2022)
The purpose of community service activities for members of the Kuntum Bloom cooperative in Tegal Village, Cikedal District, Pandeglang Regency is to be able to strengthen knowledge and ability to make budgets and savings to increase members' income. The technique of this PKM activity is interview technique, and direct observation to cooperatives. With the approach of the PAR (Participatory Action Research) method which is carried out in a participatory manner among cooperative members in a cooperative whose enthusiasm is to encourage real actions in everyday life. The results of PKM activities are 1) Can know money management strategies and increase them, 2) Understand how to prioritize spending, 3) Know how to deal with difficulties, 4) Can make savings goals for the long and short term, 5) Can identify family behavior to achieve savings goals.